ARTISTIC GLOSSES OF MELODY (Scientific journal of the Fergana State University, 2023)
This article is dedicated to the analysis of the art of character creation, using the example of N. Jaloliddin's story "Sevgi" (Love). The author's skill in creating images, highlighting the psychological aspects of the characters through details, and the use of national traditions and customs in depicting the epic narrative are analyzed with the help of examples. In the analysis, attention is paid to the poetic functions in the structural characteristics of the story, and the importance of these functions in achieving artistic perfection is determined. The author's skill is highlighted in using poetic language and vocal materials to reveal the characters' traits and to propel the plot forward. The structural, artistic, national, and educational characteristics of the work are also discussed.